Implementation of the conceptual principles of business social responsibility in ensuring rational water use - Nina Khumarova; Natalia Mahats (Економічний форум)
The article is devoted to the justification of the need to implement the conceptual principles of business social responsibility in order to ensure rational water use in Ukraine. The main purpose of the research is to determine the role of implementing the conceptual principles of business social responsibility in the context of ensuring rational water use in Ukraine. The analysis of the significant developments of foreign and domestic scientists showed that the main attention in the studies is given to the general definition of the essence of the concept of business social responsibility, directions, tools and problems of its implementation at enterprises of various sectors of the economy. However, issues related to trends in the development of socially responsible business in the water use field and the application of best practices of socially responsible business to ensure rational water resources use still require further research. The relevance of solving this scientific problem lies in the fact that Ukraine is one of the countries least supplied with fresh water in Europe, but it is characterized by a high level of man-made pressure on the water basin. Since the business sector has the greatest impact on the state of water resources, the responsibility for the negative consequences of business activities should be on business entities. The article presents the results of the analysis of the water capacity level of Ukraine's GDP, which indicate that the efficiency of water resources use in Ukraine is one of the lowest in Europe. The authors considered the components of WSS enterprises social responsibility, proposed methodical recommendations for their assessment and determined their functional dependence. Based on the analysis of trends in the development of socially responsible business in the water use field, it was proposed to apply the best global practices aimed at rational water use in Ukraine